Pole-athlete interaction during the pole vault approach phase - Needham, L.; Bezodis, I.; Exell, T.; Irwin, G. (ISBS Proceedings Archive (Michigan), 2017)
The aim of this study was to assess whether pole vaulters interacted differently with the pole during normal and perturbed approach phase conditions. Six national and international level athletes performed nine jumps, which were recorded and analysed. Pole vaulters were found to produce different coordination patterns when interacting with the pole during normal and perturbed approach phase conditions. The variable nature of the highly skilled athletes enforces the need for degenerate behaviours in achieving consistent performance outcomes. Athletes produced different coordination patterns, and should be considered on an individual basis in order to effectively, efficiently and safely improve performance.